Editorial: Supply chain management - Dimitrios Aidonis; Dimitrios Folinas; Dimitrios Triantafillou (International Journal of Business Science & Applied Management (IJBSAM), 2012)
This special issue has followed up the 2nd Olympus International Conference on Supply Chains held on October 5-6, 2012, in Katerini, Greece. The Conference was organized by the Department of Logistics of Alexander Technological Educational Institution (ATEI) of Thessaloniki, in collaboration with the Laboratory of Quantitative Analysis, Logistics and Supply Chain Management of the Department of Mechanical Engineering, Aristotle University of Thessaloniki (AUTH). During the 2-Days Conference more than 50 research papers were presented covering the following thematic areas: (i) Business Logistics, (ii) Transportation, Telematics and Distribution Networks, (iii) Green Logistics, (iv) Information and Communication Technologies in Supply Chain Management, and (v) Services and Quality. Three keynote invited speakers addressed interesting issues for the Humanitarian Logistics, Green Supply Chains of the Agrifood Sector and the Opportunities and Prospects of Greek Ports chaired Round Tables with other Greek and Foreign Scientists and Specialists.
Keywords: 650; 2nd Olympus International Conference on Supply Chains; special issue; selected papers